The Role of Islamic Symbol in Advertising among Hijabers and Non – Hijabers Using ELM Framework - Muhammad Zakky Azhari; Yeni Oktavia (Management and Leadership Study Programme, 2019)
This study investigates the effect of Islamic symbol i.e. halal logo and hijaber talent in advertising from the perspective of hijabers and non hijabers. The framework of this study is Elaboration Likelihood Model (ELM). By using experimental design and fictitious brands, this study looks into the likelihood to try of a new product among hijabers and non hijabers by controlling the high involvement and low involvement message strategy of the ad. While there is no difference of likelihood to try between hijabers and non hijabers in high involvement or central route message situation, hijabers show higher likelihood to try than non hijabers in low involvement or peripheral route context. This result indicates that Islamic symbol serves as peripheral route in advertising processing among hijabers.